Hölder’s inequality for shifted quantum integral operator - Andrea Aglić Aljinović; Lana Horvat Dmitrović; Ana Žgaljić Keko (Examples and Counterexamples)
We show by two counterexamples that Hölder’s inequality for shifted quantum integral operator does not hold in general and we prove the case in which it is valid.